BLENDED LEARNING OF NUSANTARA DANCE TO AFFECT LEARNING DANCE PRACTICE IN THE PANDEMIC PERIOD - Sumiani Sumiani; Selfiana Saenal (Universitas Negeri Makassar, 2022)
This research aims to design dance practice learning in the Sendratasik Education study program. Changes in the curriculum in response to the MBKM program will indirectly affect the learning process, where lecturers must develop their learning designs. This study followed up by designing a blended learning-based practice of Nusantara dance. Of course, this research is a step towards more effective learning for students of the Sendratasik Education Study Program who are heterogeneous in terms of their dancing abilities, also during the pandemic which has an impact on limiting face-to-face (offline). The research problem is focused on: How is the design of a valid Nusantara dance practice learning design in the Sendratasik Education Study Program, Department of Performing Arts, FSD UNM. The research step uses the ADDIE (Analysis, Design, Development, Insemination, and Evaluation) model, which in this research activity reaches the design stage. The results of the study: The design of learning design for the practice of Nusantara dance needed in the Sendratasik Education PS, Department of Performing Arts, FSD UNM, is a design that is following the learning objectives as implied in the learning outcomes (CPL) in the curriculum of the study program, that the practical ability, especially the practice of Nusantara dance, is limited to learning interests in primary and secondary education units. The learning design for the practice of Nusantara dance is based on the concept of the 10-stage Dick & Carey model, namely: identification of learning objectives for Nusantara dance, analysis of learning, identification of initial behavior and characteristics of students who are required to program, formulating learning objectives following CPL, developing criteria for reference test items that refer to three aspects (wiraga, wirama, wirasa), learning strategies are arranged according to the needs of MBKM, development of a selection of learning materials following the availability of human resources (competence of lecturers in the Department of Performing Arts), formative evaluation is carried out at the end of the middle of the semester, revision of learning is carried out by reflecting on the results formative evaluation, and summative evaluation carried out at the end of the semester